Prevalence and Molecular Characterization of Extended-Spectrum β-Lactamase Producing Enterobacterales in Healthy Community Dogs in Israel - Anat Shnaiderman-Torban; Shiri Navon-Venezia; Hadar Baron; Wiessam Abu-Ahmad; Haya Arielly; Gal Zizelski Valenci; Israel Nissan; Yossi Paitan; Amir Steinman (MDPI AG, 2022)
Background: antimicrobial resistance is a global problem in human and veterinary medicine. We aimed to investigate the extended spectrum β-lactamase-producing Enterobacterales (ESBL-PE) gut colonization in healthy community dogs in Israel. Methods: Rectal swabs were sampled from 145 healthy dogs, enriched, plated on selective plates, sub-cultured to obtain pure cultures, and ESBL production was confirmed. Bacterial species and antibiotic susceptibility profiles were identified. WGS was performed on all of the ESBL-PE isolates and their resistomes were identified in silico. Owners' questionnaires were collected for risk factor analysis. Results: ESBL-PE gut colonization rate was 6.2% (n = 9/145, 95% CI 2.9-11.5). Overall, ten isolates were detected (one dog had two isolates); the main species was Escherichia coli (eight isolates), belonging to diverse phylogenetic groups-B1, A and C. Two isolates were identified as Citrobacter braakii, and C. portucalensis. A phylogenetic analysis indicated that all of the isolates were genetically unrelated and sporadic. The isolates possessed diverse ESBL genes and antibiotic-resistance gene content, suggesting independent ESBL spread. In a multivariable risk factor analysis, coprophagia was identified as a risk factor for ESBL-PE gut colonization (p = 0.048, aOR = 4.408, 95% CI 1.014-19.169). Conclusions: healthy community dogs may be colonized with ESBL-PE MDR strains, some of which were previously reported in humans, that carry wide and diverse resistomes and may serve as a possible source for AMR.